2012
DOI: 10.1177/1362361312466962
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a broad-based screen versus disorder-specific screen in detecting young children with an autism spectrum disorder

Abstract: The goals of our study were to (a) compare agreement between autism spectrum disorder diagnosis and outcome of the Modified Checklist for Autism in Toddlers and Parents Evaluation of Developmental Status in a sample of toddlers and (b) examine specific concerns noted for toddlers who screened negative on the Modified Checklist for Autism in Toddlers or Parents Evaluation of Developmental Status but were later diagnosed with autism spectrum disorder. Participants were administered the Modified Checklist for Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…56 The M-CHAT has been shown to outperform a broadband developmental screening tool (The Parents' Evaluation of Developmental Status [PEDS]) in identifying children with ASD, suggesting that the use of a separate instrument to screen for ASD is justified. 57,58 IMPROVING SURVEILLANCE AND SCREENING While research supports the effectiveness of ASD surveillance and screening in the early identification of children with ASD, primary care pediatricians report a lack of self-efficacy in ASD surveillance and infrequently use ASD screening tools. 3,59 Pediatric residents report that learning more about ASD is important but describe their current level of training as inadequate.…”
Section: Asd Screeningmentioning
confidence: 98%
“…56 The M-CHAT has been shown to outperform a broadband developmental screening tool (The Parents' Evaluation of Developmental Status [PEDS]) in identifying children with ASD, suggesting that the use of a separate instrument to screen for ASD is justified. 57,58 IMPROVING SURVEILLANCE AND SCREENING While research supports the effectiveness of ASD surveillance and screening in the early identification of children with ASD, primary care pediatricians report a lack of self-efficacy in ASD surveillance and infrequently use ASD screening tools. 3,59 Pediatric residents report that learning more about ASD is important but describe their current level of training as inadequate.…”
Section: Asd Screeningmentioning
confidence: 98%
“…However, neither of these studies on the PEDS conducted formal ASD evaluations. A recent study by Wiggins and colleagues (27) compared the agreement of the PEDS and M-CHAT screeners with the results of a comprehensive clinical autism evaluation. While the M-CHAT demonstrated higher agreement with the clinical diagnosis, all children diagnosed with an ASD demonstrated at least one domain of concern on the PEDS, indicating good sensitivity for ASD if a fairly low threshold is used.…”
Section: Introductionmentioning
confidence: 99%
“…Examine how broadband and ASDspecific screening tools can be used 54 reported that the M-CHAT had higher sensitivity for ASD than the high-risk threshold for any area of general concern covered by the PEDS. Although the PEDS detected many children with other developmental concerns, sensitivity for ASD could not be achieved without lowering the screen-positive threshold to a level that would identify a substantial proportion of the general population (25%).…”
Section: Lack Of Office-based Systems For Making Referrals and Monitomentioning
confidence: 99%